Unstable Constitutionalism:Law and Politics in South Asia - Clarisa, Inez Devina; Angelin, Margareta Sevilla Rosa (DiH: Jurnal Ilmu Hukum, 2019)
The character of South Asian constitutionalism is desribed by unstable constitutionalism. Unstable constitusionalism refers to a phenomenon in which all participants in national politics appear to be sincerely committed to the idea of constitusionalism – if not always a fully liberal constitutionalism, then certainly one that hopes to establish reasonably permanent institusions with the capacity to address issues of daily governance – yet they stuggle to settle on a stable institutional structure embodying a form of constitutionalism appropriate to their nation. The design issues are significant; a unitary national government, symmetrical or asymmetrical federalism, confederation, and more.